BEYOND THE PASTORAL: ENVIRONMENTAL IMAGINATION IN O.A BUSHNELLS KAAAWA - Kristiawan Indriyanto (Sanata Dharma University, 2020)
This paper explores the environmental imagination in O.A Bushnells Kaaawa through his representation of pastoralism. A Hawaiian novelist, Bushnell conceptualizes his idea of pastoral based on the Hawaiians traumatic experience with the Western colonial powers. Different with the Anglo-American discourse of pastoralism which emphasizes more on the individual self and the reorientation toward the natural world in rural area, Bushnell foregrounds the far-reaching impact of colonialism which affects even the periphery of Oahu island. The titular village of Kaaawa, previously a sacred place where the inhabitants with the blessing of Hawaiian gods lived bountiful with nature also suffers the outbreak of Western diseases. Instead of a place for reorientation and rejuvenation, Bushnells concept of pastoralism in Kaaawa evoke the traumatic experience of the islanders in which the picturesque landscape of Hawaii represents the silent witness towards the desolation of Hawaiian archipelago. To reiterate, this paper argues how Bushnell orients his work within the socio-historical background of Hawaii and deliver a critique towards the impact of colonialism towards the islanders through his conception of pastoral.